Performance, the Arts, and Curricular Change (LEARNing Landscapes, 2020)
The need to improvise and take action as a practitioner draws on Schwab’s notion of deliberation and the Greek concept of poiesis. Inspired by an impromptu discussion with students at a computer summer camp, the author uses the worksof Sarason, Eisner, and Stenhouseto show how practitioner performance, student audience, educational inquiry, teacher as researcher, and curricular change are interrelated.
Keywords: deliberation; poiesis; performance; art; curricular change